Highly efficient production of transgenic rats with long DNA insertions using piggyBac transposase mRNA and piezo-assisted microinjection - Kohtaro Morita; Shunya Ihashi; Eiichi Okamura; Kazuya Goto; Toru Yoshihara; Arata Honda; Masatsugu Ema; Masahide Asano (PLoS ONE, 2026)
In the conventional method of producing transgenic (Tg) animals, donor DNA is microinjected into the pronuclei of zygotes using a sharp glass needle. However, this approach is generally inefficient as it requires highly skilled microinjection techniques to ensure zygote survival and the transgene is incorporated into only a small proportion of the offspring. In contrast, methods based on piggyBac transposase (PBase) enables more efficient insertion of DNA into the genome and generation of Tg animals. The use of piggyBac transposase have also been examined in rats→ However, this method has not yet been fully optimized or properly characterized. In this study, we examined the microinjection of PBase mRNA and donor plasmid DNA into the pronuclei of rat zygotes using piezo-assisted microinjection. This approach resulted in high survival rates and enabled the efficient generation of Tg rats, even with long donor DNA. When the zygotes were microinjected using Piezo, over 70% were viable, and after embryo transfer, over 80% of the pups carried the transgene. Furthermore, we confirmed germline transmission to the F1 and F2 generations. We also attempted to generate a rat model of Alzheimer’s using this method→ However, the protein was not detected despite mRNA expression, and the phenotype was not observed in behavioral tests. Although the generation of Alzheimer’s disease model remains a challenge, our findings show that piggyBac transposase mRNA combined with piezo-assisted microinjection represents a simple and efficient method for producing Tg rats, even with long donor DNA.